Human resource management : (for BBA (4th semester) students of WBUT) - Gupta, Shashi K (Kalyani Publishers, 2011)
Human resource management : (for BBA (4th semester) students of WBUT) / Gupta, Shashi K.. -- Kolkata: Kalyani Publishers, 2011 658.3 G978e2 2nd rev. ed. No. of Copies : 1